Numerical model and experimental validation of the electrical and thermal performances of photovoltaic/thermal plant. (15th September 2020) - El Fouas, C.; Hajji, B.; Gagliano, A.; Tina, G.M.; Aneli, S.
Abstract: The technology of photovoltaic-thermal solar collectors offers an attractive option for the simultaneous production of electrical and thermal energies. This technology finds interesting applications in the fields of desalination, sensitive heating/cooling and other related industrial processes. In this paper, we study the performance of a photovoltaic-thermal solar power plant operating in a Mediterranean city (Catania, Italy). A novel numerical model for a solar plant, constituted by uncovered photovoltaic-thermal solar collectors, the hydronic and electric circuits, and thermal solar tank, is presented and validated with experimental data. The developed model, based on energy balance equations for each Photovoltaic-Thermal Solar plant component, allows determining the state and dynamic behaviour of the system. The set of equations attained is resolved via the Runge-Kutta (RK4) numerical method in MATLAB software. Moreover, the built model allows considering the effects of solar radiation, outdoor temperature, wind velocity, the temperature in the thermal storage, flow rate and features of the photovoltaic-thermal solar panel, on the electrical and thermal energy production. The performances of the photovoltaic-thermal solar power plant have been evaluated and analysed. In particular, hourly temperatures achieved in the solar tank as well as the voltage in open circuit condition are calculated and compared with the observed experimental data. Furthermore, such analysis highlights a very good correlation between experimental and simulated results with a coefficient of determination higher than 0.96 and a root mean square error lower than 7%. During the period of survey, the investigated Photovoltaic-Thermal Solar plant provide an average daily energy production of 0.83 kWh/m 2 of electrical energy and 0.53 kWh/m 2 of thermal energy.